Respuesta :
Answer:
x= k/a-b
Step-by-step explanation:
Move all terms to the left side and set equal to zero as well as each factor.
Hope this helps.
Answer: a = b + kx^-1
Step-by-step explanation:
Simplifying
ax + -1bx = k
Solving
ax + -1bx = k
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add 'bx' to each side of the equation.
ax + -1bx + bx = bx + k
Combine like terms: -1bx + bx = 0
ax + 0 = bx + k
ax = bx + k
Divide each side by 'x'.
a = b + kx^-1
Simplifying
a = b + kx^-1